Menstrual irregularity and its associated factors among college students in Ethiopia, 2021 - Yohannes Moges Mittiku; Haile Mekonen; Girma Wogie; Michael Amera Tizazu; Getu Engida Wake (Frontiers Media S.A., 2022)
BackgroundMenstrual irregularity can occur at any age, but it is most common among women under the age of 23 years. Menstrual irregularity is a foremost gynecological problem and a cause of anxiety to students and those close to them. These students experience monthly absenteeism, premenstrual symptoms, and a lack of concentration due to menstrual problems, all of which interfere with their education. Therefore, this study aimed to assess the magnitude of menstrual irregularity and associated factors among college students in Debre Berhan Town, North Shewa, Amhara Regional State, Ethiopia, in 2021.MethodsAn institution-based cross-sectional study was conducted from June to July 2021 in Debre Berhan town. Data was collected using self-administered questionnaires in 420 eligible female college students by systematic random sampling technique. Weight and height were measured and Body Mass Index (BMI) was calculated after data collection. Each questionnaire was checked for completeness, cleaned, coded, entered into EPI-DATA, and then transported to SPSS software. Bi-variable and multivariable logistic regression analyses were employed to determine the association of each independent variable with the dependent variable. P ≤ 0.05 were used to declare association and select predictors.ResultsIn the current study, 395 students participated with a response rate of 93.6%. Of all the total respondents, the magnitude of menstrual cycle irregularity was 33.4% (95% CI 28.6-38.2). Age < 20 years old [AOR = 3.88, 95% CI (1.25-12.18)], age of menarche ≤ 12 years [AOR = 4, 95% CI (1.18-13.9), sleeping hours ≤ 5 h [AOR= 2.26, 95% CI (1.04-4.93)], perceived stress [AOR = 2, 95% CI (1.53-3.23)] and being overweight [AOR = 2, 95% CI (1.13-3.23) were the variables significantly associated with the magnitude of menstrual irregularity.Conclusion and recommendationThis study shows that more than one-third of the college students in Debre Berhan town have experienced menstrual irregularity. Being less than 20 years old, having a history of early menarche, being overweight, and perceived stress were a variable significantly associated with menstrual irregularity. To control menstrual irregularity, girls should control their weight and lead a healthy lifestyle, including getting adequate sleep which could be aided by training on time management.